MRI assessment of tissue effects after 180‐W XPS greenlight laser vaporization of the prostate. Issue 6 (11th April 2017) - Huet, Romain; Mathieu, Romain; Rohou, Tanguy; Peyronnet, Benoit; Manunta, Andrea; Verhoest, Gregory; Bensalah, Karim; Vincendeau, Sebastien
Abstract : Background and Objective: Photoselective vaporization of the prostate (PVP) is an alternative to transurethral resection of the prostate (TURP) in the surgical management of Benign Prostate Obtruction (BPO), with a better hemostatic effect due to a coagulation depth of several millimeters. The objective of this study was to prospectively assess the tissue effects of PVP by Magnetic Resonance Imaging (MRI). Materials and Methods: From December to February 2014, ten patients were included in a prospective study and underwent PVP performed by a single surgeon with the Greenlight™ laser 180‐W XPS. A multiparametric MRI of the prostate (Siemens 3T Verio) was achieved the day before the procedure and post‐operatively (2 days, 7 days, 3 and 6 months after the procedure). The prostate volume after tissue removal was determined. The depth of necrosis in the prostatic and peri‐prostatic tissues were assessed at six different locations. Results: The median age and pre‐operative prostate volume were 70 years (64–76) and 48.1 ml (19–74.4), respectively. Median prostate volume significantly decreased post‐operatively ( P  < 0.001): At 6 months, median prostate volume reduction was 44.2% (38.7–49.5) ( P  = 0.001) compared to pre‐operative setting. Two and 7 days after the procedure, mean depths of necrosis were 2.5 mm (0–3) and 1.3 mm (0–2.4), respectively. No necrosis was reported 3 and 6 months after the procedure. Conclusions: PVP with Greenlight™ XPS 180‐W is associated with a significant reduction of prostate volume. The depth of necrosis is low and homogeneous, resulting in a limited risk of peri‐operative complications. Lasers Surg. Med. 49:577–581, 2017. © 2017 Wiley Periodicals, Inc.